PENGEMBANGAN MEDIA e-PocketBook MENGENAI AKTIVITAS FISIK DALAM UPAYA PENCEGAHAN DIABETES MELITUS PADA REMAJA DI SMA KARTIKA XIX-3 BANDUNG - Zain, Adjeng Afitalia; Setiawan, Ridwan (Politeknik Kesehatan Kemenkes Bandung, 2024)
Adolescent knowledge about the risk factors of diabetes mellitus is certainly very concerning. In addition, many young people, especially in the school environment, do not know how to take early prevention to avoid diabetes mellitus. This study aims to develop educational media in the form of an electronic pocket book on physical activity that can be implemented as an effort to prevent diabetes mellitus in adolescent, especially student of SMA Kartika XIX-3 Bandung. The method used in this research is the ADDIE model which consists of five stages, namely analysys, design, development, implementation, and evaluation. The subjects in this study were students of SMA Kartika XIX-3 Bandung and the research sample amounted to 66 grade student 10. In this study, students were given knowledge about diabetes mellitus using pretest and posttest question totaling 15 question. Based on the result of the study, students knowledge about the importance of physical activity in preventing diabetes mellitus will increase. This is an increase in knowledge 21%. The result of the pretest obtained a value of 68, while the result of the posttest obtained a value of 89. The use of e-PocketBook media has a significant influence on student knowledge in efforts to prevent diabetes mellitus in adolescent at SMA Kartika XIX-3 Bandung. In addition, the use of e-PocketBook media as a learning media is expected to be an innovative solution in adolescent health education.